2018
DOI: 10.1039/c7cy02329d
|View full text |Cite
|
Sign up to set email alerts
|

Au–Pd NPs immobilised on nanostructured ceria and titania: impact of support morphology on the catalytic activity for selective oxidation

Abstract: Bimetallic Au-Pd nanoparticles supported on different ceria and titania nanostructures have been prepared by sol-immobilisation, and evaluated in the solvent-less selective oxidation of benzyl alcohol. The catalysts were characterised by TEM, STEM, XRD, XPS, ICP-AES, and nitrogen adsorption-desorption measurements.The activity of the catalysts was found to be strongly related to the morphology, structure and physiochemical properties of the supports. Au-Pd/ceria nanorods exhibited remarkably high catalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 63 publications
4
23
0
2
Order By: Relevance
“…Based on the observed Pd and Au elements on the cata-lysts by using XPS, the molar ratios of Au/Pd were calculated and ranked by ACP > ACR > ACC. These values based on the XPS characterization were found lower than the nominal Au/Pd values, which suggests the enrichment of Pd species on CeO2 surface, the si-milar phenomenon was also reported by David et al, which could be assigned to the variation in XPS analysis depths between Pd and Au [15].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Based on the observed Pd and Au elements on the cata-lysts by using XPS, the molar ratios of Au/Pd were calculated and ranked by ACP > ACR > ACC. These values based on the XPS characterization were found lower than the nominal Au/Pd values, which suggests the enrichment of Pd species on CeO2 surface, the si-milar phenomenon was also reported by David et al, which could be assigned to the variation in XPS analysis depths between Pd and Au [15].…”
Section: Resultssupporting
confidence: 61%
“…Liu et al synthesized CeO2 rod under the protection of N2 followed by in-situ load of Au and Pd nanoparticles applying surface redox mechanism between CeO2 and noble metal to produce AuPd/CeO2 rod catalyst, which showed high benzyl alcohol conversion and benzaldehyde selectivity [14]. David et al also prepared Au-Pd/CeO2 nanorod catalyst with sol-immobilization method using NaBH4 as a reducing agent, which exhibited high catalytic activity in the same reaction under solvent-free condition [15]. In addition, Au-Pd supported on ceria-zirconia mixed oxide was also applied for the benzyl alcohol oxidation, a synergistic effect existed between Au and Pd during the reaction [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the higher ratios of Pd 2+ on the ATR and ATB indicated that the TiO 2 carrier also played an essential role in promoting the formation of Pd 2+ , which could supply oxygen to assist the production of Pd 2+ . The existence of Pd 2+ species further demonstrates that some Pd cannot alloy with Au; this phenomenon has been reported in the similar Au-Pd/CeO 2 catalyst [18]. The XPS spectra of O1s on the ATA, ATB, and ATR catalysts are exhibited in Fig.…”
Section: Resultssupporting
confidence: 75%
“…The use of microwave is regarded as much more effective, when compared with conventional heating, usually with similar yields achieved in a shorter time and at lower temperatures (Varma, 2007; Dudley et al, 2015). Other authors also used TBHP (Choudhary and Dumbre, 2009a,b, 2010; Choudhary et al, 2009; Li H. R. et al, 2009; Peneau et al, 2013; Zhang B. et al, 2016; Martins et al, 2017; Ndolomingo and Meijboom, 2017; Gogoi et al, 2018; Kashani et al, 2018) and H 2 O 2 (Zhan et al, 2012, 2013; Hallett-Tapley et al, 2013; Moreno et al, 2013; Santonastaso et al, 2014; Tang et al, 2014; Long and Quan, 2015; Mehri et al, 2015; Restrepo et al, 2015a,b; Emayavaramban et al, 2016a; Zhang B. et al, 2016; Gogoi et al, 2018; Khawaji and Chadwick, 2018; Tareq et al, 2018) as oxidants for alcohol oxidation reactions, although more studies deal with the use of oxygen (Besson and Gallezot, 2000; Prati and Porta, 2005; Bond et al, 2006; Hashmi and Hutchings, 2006; Hutchings et al, 2006; Carabineiro and Thompson, 2007, 2010; Ishida and Haruta, 2007; Fristrup et al, 2008; Della Pina and Falletta, 2011; Della Pina et al, 2012; Dimitratos et al, 2012; Takei et al, 2012; Hutchings, 2014; Freakley et al, 2015; Sharma et al, 2016).…”
Section: Alcohol Oxidationmentioning
confidence: 99%